2009
DOI: 10.1177/030089160909500606
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Long-Term Results and Prognostic Factors of Postoperative Treatment for UICC Stages II and III Rectal Cancer

Abstract: Our retrospective study showed a good 5-year local control. Factors such as individual pT4, pN1, pN2, age > or = 70 years, abdominal-perineal resection, stages IIIB-IIIC versus II-IIIA and extraperitoneal tumor location negatively influenced disease-free survival, distant metastases and cancer-specific survival. Differences exist between stages II and III rectal cancer and treatment modulation and intensification are required in order to offer the most appropriate and effective adjuvant treatment and to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Data from Genovesi et all confirmed these evaluations in the multivariate analysis, with a negative influence of extraperitoneal tumor location on DFS and CSS. 29 In this present study the carsinomas presenting at the lower rectum also had 40% 5 years survival which is comparable to the other studies as well. Pathological studies of the Circumferential Resection magrin (CRM) at the level of the anorectal junction and anal canal sphincter show higher rates of CRM involvement due to dissection along the thinning mesorectum on to the anal sphincter.…”
Section: -14supporting
confidence: 91%
“…Data from Genovesi et all confirmed these evaluations in the multivariate analysis, with a negative influence of extraperitoneal tumor location on DFS and CSS. 29 In this present study the carsinomas presenting at the lower rectum also had 40% 5 years survival which is comparable to the other studies as well. Pathological studies of the Circumferential Resection magrin (CRM) at the level of the anorectal junction and anal canal sphincter show higher rates of CRM involvement due to dissection along the thinning mesorectum on to the anal sphincter.…”
Section: -14supporting
confidence: 91%
“…Univariate analysis showed that in this study the well known prognostic factors, such as TNM stage, performance status, CEA serum level, resection margins, perineural, vascular and lymphatic invasion, node capsular effraction and recurrences [ 13 17 ] have statistically significantly influenced overall survival ( Table IV ).…”
Section: Discussionmentioning
confidence: 55%
“…The frequency of follow-up is still debatable. With a moderate consensus, it was agree that the selection of patients for a tailored follow-up based on tumor stage and patient age is important [37][38][39] . Surveillance beyond the 5th year after the diagnosis is recommended in patients submitted to preoperative therapies.…”
Section: Evidencementioning
confidence: 99%